2014
DOI: 10.4236/ojpc.2014.42011
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation Constant of N-(2-Acetamido)-Iminodiacetic Acid Monosodium (ADA) from (278.15 to 328.15) K

Abstract: The acidic dissociation constant of N-(2-acetamido)-iminodiacetic acid monosodium (ADA) has been determined at 12 temperatures from 278.15 to 328.15 K by electromotive-force (emf) measurements of hydrogen-silver chloride cells without liquid junction. At 298.15 K, the value of the dissociation constant (pK 2 ) is 6.8416 ± 0.0004. In response to the need for new physiological pH standards, buffer solutions of NaADA and its disodium salt, Na 2 ADA would be useful for pH control in the biological region of pH 6.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Values of E ‚ 4 and 2.3026RT/F in absolute volts are summarized in an earlier publication [33]. The ionic strength ( I $ ) of the solution in the cell A [25] is given by equation 3= r + + ( ) From dissociation of H ' Mal in different solvents composition, 10, 20, and 30% ethylene glycol-water mixed solvent, the apparent first dissociation constant pK … $ , was calculated from equation [23]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Values of E ‚ 4 and 2.3026RT/F in absolute volts are summarized in an earlier publication [33]. The ionic strength ( I $ ) of the solution in the cell A [25] is given by equation 3= r + + ( ) From dissociation of H ' Mal in different solvents composition, 10, 20, and 30% ethylene glycol-water mixed solvent, the apparent first dissociation constant pK … $ , was calculated from equation [23]…”
Section: Resultsmentioning
confidence: 99%
“…There are four General methods for the measurement of dissociation constant of carboxylic acid, including Potentiometric titration method [5] [6] [7] [8], Conductometric method [9][10] [11], Spectrophotometric methods [12] [13] [14], and Electromotive force measurement method [15][16] [17]. There are many studies on dissociation constant of carboxylic acid in different organic-water mixed solvents and at different temperatures [18] [25]. The present work involved the determination of the first and second dissociation constants (pK $ & pK ' ) of malonic acid in different composition of ethylene glycol-water, (EG-water) mixed solvent, (10%, 20% and 30%) using the electromotive force measurements of galvanic cells without liquid junction containing standard hydrogen electrode and silver-silver chloride electrode at different temperatures in the range (278.15 − 318.15K ) at 5° interval.…”
Section: Introductionmentioning
confidence: 99%
“…At 298.15 K, the standard deviation between the initial and the middle e.m.f reading was ±0.04 mV. The preparation of the thermal electrolytic type Ag-AgCl electrode, the hydrogen electrode, the design of cells [3] [4], and other experimental details have been described in previous publications [9]- [11]. The e.m.f values have been corrected, as usual, to the partial pressure of one atmosphere of dry hydrogen.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Piperazine-N,N′-bis-2-hydroxypropanesulfonic acid (POPSO sesquisodium salt) is a water soluble solid of considerable interest as a physiological buffer [1] for the control of pH between (7.0 and 8.5). Very recently, we have reported the values of the second dissociation constant (pK 2 ) of 2,2-bis(hydroxymethyl)-2,2′,2″-nitrilotriethanol (BIS-TRIS) [2], N-(2-acetamino)-iminodiacetic acid monosodium (ADA) [3] and monosodium 1,4-piperazinediethanesulfonate [4] from (278.15 to 328.15) K. Hetzer et al [5] have determined pK 2 values of PIPERAZINE, the parent compound of (POPSO), from (273.15 to 323.15) K. Thiel et al [6] did not provide any pK 2 value for (POPSO) but they did study the effect of pH on the variation of enzyme activity and growth of bacterial strain with some zwitterionic buffers including Good Buffer (POPSO) [1] [7]. Goldberg et al [8], in their comprehensive review article, reported that no accurate thermodynamic data of pK 2 and related thermodynamic quantities for POPSO sesquisodium salt are available in literature.…”
Section: Introductionmentioning
confidence: 99%